2014
DOI: 10.1007/s10853-014-8661-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the strength loss of glass fibre after thermal conditioning

Abstract: Single fibre tensile testing of thermally conditioned water sized and γ – aminopropyltriethoxysilane (APS) sized boron-free E-glass has been carried out. The fibres were produced from identical melts following which bare fibre had only water applied to it before winding whereas the sized fibre had a solution containing only APS applied to its surface. Both fibre types experience a loss of room temperature tensile strength after exposure to elevated temperature. By application of a novel method of single fibre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 21 publications
8
53
0
Order By: Relevance
“…The fibres after soxhlet extraction exhibit strengths close to the one obtained for the pristine fibres with no significant difference. They are however close to strengths measured on bare E-glass fibres [11]. It should be noted that a compliance correction have not been executed since only one gauge length was used.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The fibres after soxhlet extraction exhibit strengths close to the one obtained for the pristine fibres with no significant difference. They are however close to strengths measured on bare E-glass fibres [11]. It should be noted that a compliance correction have not been executed since only one gauge length was used.…”
Section: Resultssupporting
confidence: 76%
“…The strength of the pristine fibres are much lower than values given in literature [2,3,19] from which a strength of around 3 GPa was expected. The burned fibres do however still follow the decreasing tendency and have similar values as found in literature [11][12][13]20]. The low strength is related to enlargement of existing surface flaws that become vulnable to attack from water [20].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Due to the harsh conditions employed in this procedure, the glass fibres suffer from a severe loss in their ultimate strength and therefore cannot be reused in many forms of composite applications [7][8][9][10]. We have recently developed a simple chemical approach to address this key issue and have successfully proved that these damaged filaments can be reused as reinforcements again if their strength is restored [11].…”
Section: Introductionmentioning
confidence: 99%
“…Jenkins et al [41] also confirmed the effect of thermal conditioning on the single fibre strength of these same APS sized and bare GF. They observed that many researchers studying this strength loss phenomenon carried out the heat conditioning process on the "as-received" fibre roving or mats.…”
Section: The Role Of Silanes and Sizingsmentioning
confidence: 70%